Stearic Acid Esters Synthesized using Iron Exchanged Montmorillonite K10 Clay Catalysts - Enas A. Almadani; Salina M. Radzi; Farah W. Harun (Research India Publications, 2024)
In this study the effects of reaction parameters for production of stearic acid esters catalyzed by cation exchanged montmorillonite K10 (MMT K10) were studied. Iron exchanged MMT K10 (Fe-MMT K10) with four different concentrations of Fe3+ ( 0.25 M, 0.5 M, 0.75 and 1 M) catalysts were used to catalyze the esterification reaction of stearic acid with two alcohols i.e. ethanol and methanol. The catalysts were prepared via cation exchanged method and characterized by X-ray powder diffraction (XRD), scanning electron microscopy (SEM) equipped with energy dispersive x-ray (EDX), thermal gravimetric analysis (TGA), and the acidity of catalysts was measured using pyridine adsorption technique monitored by FTIR spectroscopy. The effects of various reaction parameters such as catalysts concentration, reaction time and type of alcohol have been investigated. High stearic acid conversion reached up to 75% for reaction conducted with methanol at 80 oC was obtained when 0.75 M and 1 M Fe-MMT K10 were used as the catalysts. This suggests that the cation exchanged MMT K10 can be a potential catalyst for industrial applications.